Peningkatan Hasil Belajar IPA Kompetensi Sistem Reproduksi Manusia Melalui Model Kooperatif Numbered Heads Together (NHT) Berbantuan Multimultimedia Interaktif - Izach, Mersye (Universitas Pendidikan Indonesia Kampus Serang, 2021)
The aims of this research were (1) to describe the implementation of science learning of reproductive system competence through the NHT type cooperative model assisted by interactive multimedia and (2) to improve science learning outcomes of human reproductive system competence of class IX-2 students of SMP Negeri 6 Halmahera Utara in the first semester of the 2019/2020 academic year through a NHT type cooperative model assisted by interactive multimedia. This research was action research which consists of planning, implementation, observation and reflection stages. The subjects of this study were students of class 9th graders of SMP Negeri 6 Halmahera Utara, North Maluku Province, which were 32 students. Sources of data in this study in the form of observations of the implementation of learning to measure the quality of the process, and written tests to measure student learning outcomes on reproductive system competence. The data analysis technique used was descriptive based on qualitative analysis with percentages or descriptively qualitatively. Analysis of learning outcomes test data on the competence of the human reproductive system showed that completeness in the pre-cycle 37.5% or 12 students succeeded in obtaining 67 score. In the first cycle, 62.5% students completed or as many as 20 students, while in the second cycle, 27 students completed. students (84.4%) managed to get a score of 67. Based on the results of the discussion in this study, it can be concluded that the NHT type cooperative learning model assisted by interactive multimedia is effective for improving science learning outcomes of the human reproductive system in 9th graders of SMP Negeri 6 Halmahera Utara.